Light-induced enhancement of exciton transport in organic molecular crystal - Xiao-Ze Li; Shuting Dai; Hong-Hua Fang; Yiwen Ren; Yong Yuan; Jiawen Liu; Chenchen Zhang; Pu Wang; Fangxu Yang; Wenjing Tian; Bin Xu; Hong-Bo Sun (Opto-Electronic Advances)
Efficient exciton transport over long distances is crucial for organic optoelectronics. Despite efforts to improve the transport properties of organic semiconductors, the limited exciton diffusion remains a significant obstacle for light-harvesting applications. In this study, we observe phenomena where exciton transport is significantly enhanced by light irradiation in the organic molecular crystal of 2,2'-(2,5-bis(2,2-diphenylvinyl)-1,4-phenylene) dinaphthalene (BDVPN). The exciton transport in this material is improved, as evidenced by the increased diffusion coefficient from 10−3 cm2·s−1 to over 1 cm2·s−1 and a prolonged diffusion length from less than 50 nm to nearly 700 nm characterized by time-resolved photoluminescence microscopy (TPLM). Additionally, we confirmed the enhancement of charge transport capability under irradiation as additional evidence of improved transport properties of the material. These intriguing phenomena may be associated with the material’s twisted molecular conformation and rotatable single bonds, which facilitate light-induced structural alterations conducive to efficient transport properties. Our work provides a novel insight into developing organic semiconductors with efficient exciton transport.